Analisis Manajemen Sumber Daya Manusia dalam Meningkatkan Mutu Pelayanan Kesehatan - Putu Ratih Pravitasari; Kadek Ayu Dwijuliasri (SENTRI: Jurnal Riset Ilmiah, 2026)
Human resource management (HRM) plays an important role in improving the quality of healthcare services in hospitals and other healthcare facilities. Effective HRM practices, including workforce planning, recruitment, training, competency development, performance evaluation and employee motivation, can improve healthcare service quality and patient satisfaction. This study aimed to analyze the role of human resource management in improving healthcare service quality using a literature review method. The literature search was conducted systematically using the Google Scholar database with publication period from 2021 to 2025. The selected articles were scientific publications relevant to healthcare human resource management and healthcare service quality. Based on the literature selection process, 14 articles were included in this study. The findings of the literature review revealed that healthcare workers competency development, continuous training, work discipline, organizational culture, work environment and the utilization of information technology significantly influence the improvement of healthcare service quality. Proper HRM management can enhance service effectiveness, healthcare workers professionalism, patient safety and public satisfaction with healthcare services. The literature review also identified several challenges, including limited healthcare personnel, unequal workforce distribution, limited training opportunities and suboptimal technology adaptation. Therefore, structured, systematic and sustainable HRM practices are necessary to support the continuous improvement of healthcare service quality.